Filsafat dan Estetika Menurut Arthur Schopenhauer - Elsa Magdalena; Destri Natalia; Andry Pranata; Nicolhas Jurdy Wijaya (Clef: Jurnal Musik dan Pendidikan Musik, 2022)
Aesthetics is a branch of philosophy, which specifically discusses beauty and taste, how they can be formed, and how they can be enjoyed. Beauty is not only about things that can be seen, but also about things that can be heard. Depending on the assessment objectively and subjectively. Music also has aesthetic value. It depends on what theory is used to judge the beauty of the music. This research uses descriptive-qualitative with a literature approach. In this case, it is not only about aesthetics, but also literature on music, and philosophers who discuss aesthetic philosophy.